Heart rate variability in diabetes: evidence of autonomic dysfunction across age groups - Zafar, Usman; Jawad, Muhammad; Ansar, Farrukh; Hafeez, Ehtsham; Zareef, Adil (International Journal of Pathology, 2025)
Background: Heart rate variability (HRV) serves as a non-invasive marker of autonomic nervous system function. In individuals with diabetes mellitus, cardiac autonomic neuropathy is a recognized complication that may manifest as reduced HRV and increased heart rate (HR). This study aimed to assess differences in HR and HRV between diabetic and non-diabetic individuals and explore age-related variations. Methods: A total of 64 subjects were included, comprising 33 individuals with diabetes and 31 non-diabetic controls. Short-term ECG recordings were analyzed to calculate average HR and HRV. Participants were further divided into ten age groups spanning 26–85 years, and subgroup analyses were performed to examine trends across age brackets. Results: Diabetic participants had a higher average heart rate (86 bpm) compared to non-diabetics (77 bpm), along with significantly lower HRV (0.0185 vs. 0.0333). Age-stratified analyses revealed a consistent pattern of higher HR and lower HRV among diabetic individuals across most age groups. In the 41–45 age group, diabetics exhibited an average HR of 89 bpm and HRV of 0.0179, whereas non-diabetics had 77 bpm and 0.0358, respectively. in the 56–60 age group, diabetic participants had an average heart rate of 85 bpm and an HRV of 0.0136, whereas non-diabetic participants had a lower average heart rate of 73 bpm and a higher HRV of 0.0262. Conclusion: This study reveals that diabetes is associated with reduced autonomic flexibility, as reflected by lower HRV and elevated HR. These alterations suggest early cardiac autonomic dysfunction, which may increase cardiovascular risk. Routine HRV assessment could enhance clinical monitoring and risk stratification in diabetic patients, particularly when combined with emerging digital health technologies.